MINERALOGICAL-GENETIC MODEL OF THE ZAVALLYA GRAPHITE DEPOSIT - Burban, K.; Skakun, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Graphite mineralization has been formed after metamorphic processes of amfobolite and granulite facies. Process of graphite's formation is syndeformative (deformations are between plastic and brittle). Formation of graphite are accompanied with processes of dissolution and recrystallization of quartz with growth of grain size. Mineral associations of graphite in various types of Zavallya deposit have been investigated. The most widespread associations are: graphite + Mg-Fe mix-layered silicates, graphite + sericite + albite + calcite, graphite + K-Ba feldspars. Mineral associations are typical moderate-T hydrothermal. Graphite precipitates from hydrothermal solution due to mixing of 2 CO - bearing fluid from carbonate rocks and deep 4 CH – 2 6 CH – 2 HS– bearing fluids.